Electrodiagnosis in Clinical Neurology - The Challenge for Pediatric Neurology in Indonesia - Irawan Mangunatmadja; A. C. Van Huffelen; R. H. J. M Gooskens (Paediatrica Indonesiana, 1996)
IntroductionIn most cases the diagnosis in neurology is based upon clinical manifestations, anatomical abnormalities, physiological disturbances and biochemical investigations. Clinical manifestations can be investigated by history of illness and neurological examinations. Neurophysiological examination (electrodiagnosis) can provide information on physiological abnormalities of the central nervous system (CNS). In recent years computer tomography (CT) and magnetic resonance imaging (MRI) have made it possi¬ble to visualize the morphologic anatomy of the CNS in detail and to diagnose the lesion.1IntroductionIn most cases the diagnosis in neurology is based upon clinical manifestations, anatomical abnormalities, physiological disturbances and biochemical investigations. Clinical manifestations can be investigated by history of illness and neurological examinations. Neurophysiological examination (electrodiagnosis) can provide information on physiological abnormalities of the central nervous system (CNS). In recent years computer tomography (CT) and magnetic resonance imaging (MRI) have made it possible to visualize the morphologic anatomy of the CNS in detail and to diagnose the lesion.1